Evaluation of Pentavalent Tc-99m DMSA Scintigraphy in Small Cell and Nonsmall Cell Lung Cancers - Atasever, T.; Gündoğdu, C.; Vural, G.; Kapucu, L. Ö.; Karalezli, A.; Ünlü, M. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: The purpose of this study was to evaluate the clinical usefulness of Tc-99m (V) DMSA in patients suspected of lung cancer and determine whether this agent may have value in differentiation between small cell (SCLC) and non-small cell (NSCLC) lung carcinoma. Methods: Thirty-six patients with clinical and radiological suspicion of primary lung carcinoma were injected 450-600 MBq of Tc-99m (V) DMSA intravenously. Whole body and planar anterior, posterior thorax images were obtained 4-5 h after injection of the radioactive complex. Results: Histo-pathological results confirmed 23 NSCLC, 10 SCLC and 1 metastatic lung carcinoma and 2 lung abscess. Nineteen of the 23 (82%) NSCLC and all of the 10 (100%) SCLC cases showed Tc-99m (V) DMSA uptake. Single metastatic lung cancer also accumulated radiotracer. Lung abscess did not show uptake. Lesion/Nonlesion (L/N) ratio of SCLC (1.59 ± 0.32) and NSCLC (1.43 ± 0.19) tumour types did not show statistical difference (p >0.05). Tc-99m (V) DMSA whole body imaging also showed bone metastases. Conclusion: Tc-99m (V) DMSA is a noninvasive and cheap imaging method to detect malignant lung cancers and their bone metastases but, differentiation of SCLC and NSCLC is not possible.
Keywords: Tc-99m (V) DMSA; lung tumors; small cell lung cancer; non-small cell lung cancer; inflammatory lesions